THE POTENTIAL APPLICATION OF ESD-STEAM IN IPAS PROJECT LEARNING AT VOCATIONAL HIGH SCHOOLS - Sukandani, Eny; Khoiri, Nur; Patonah, Siti (Jurnal Pendidikan Matematika dan IPA, 2026)
The rapid development of science and technology in the 21st century demands educational transformation that prepares students not only to master knowledge but also to apply it in solving real-world problems. However, learning in Vocational High Schools (SMK) often still focuses on cognitive achievement rather than developing competencies related to sustainability and innovation. This study aims to explore the potential application of the Science, Technology, Engineering, Arts, and Mathematics (STEAM)-based Education for Sustainable Development (ESD) approach in Natural and Social Sciences (IPAS) project learning in Vocational High Schools (SMK). The research method used is qualitative descriptive with a literature review approach (library research), examining various sources from accredited national and international journals, conference proceedings, and educational policy documents. Data analysis was conducted using content analysis techniques to identify themes, patterns, and relevant findings from the literature. The research results indicate that the application of ESD-STEAM in IPAS project-based learning at SMK has great potential in enhancing 21st-century competencies, such as critical thinking, creativity, collaboration, and communication skills. Additionally, this approach integrates sustainability concepts with contextual project-based problem-solving, enabling students to apply knowledge practically in social, environmental, and technological contexts. These findings align with previous research demonstrating that the integration of ESD and STEAM can enhance science literacy, environmental awareness, and readiness for a sustainable workforce.